Underlying drivers of decade-long fluctuation in the global mean sea-level rise - Hyeonsoo Cha; Jae-Hong Moon; Taekyun Kim; Y Tony Song (Environmental Research Letters, 2021)
Natural climate variability can mask the background trend of global mean sea-level (GMSL) caused by global warming. Recent advances in satellite measurements and ocean heat-content estimates have enabled the monitoring of GMSL budget components and provide insights into ocean effects on the Earth’s energy imbalance and hydrology. We observed a decadal fluctuation in GMSL rise, which coincides with an increasing trend in the 2010s after the warming ‘hiatus’ during the 2000s, and demonstrated that the rate of sea-level rise can be attributed to climate-related decadal fluctuations in ocean heat storage and hydrology. Since ∼2011, the decadal climate variability has resulted in additional ocean mass gain (271 ± 89 Gt yr ^−1 ) from glacier-free land water storage and increased ocean heat uptake (0.28 ± 0.17 W m ^−2 ), increasing the GMSL rise rate by 1.4 ± 0.4 mm yr ^−1 . The suggested estimates of sea-level and Earth’s energy budgets highlight the importance of natural variability in understanding the impacts of the ongoing sea-level rise.